KETIDAKADILAN SUBSTANSIAL DAN KEKERASAN SIMBOLIK DALAM PROBLEM MARGINALISASI ANAK BERKEBUTUHAN KHUSUS DI SURAKARTA - Theofilus Apolinaris Suryadinata (Jurnal Analisa Sosiologi, 2024)
This research leads to the marginalization of children with special needs  in Surakarta, Central Java. The self-development of a human being determined both genetically and in the social environment has implications for different abilities both physical and mental. In society, there are often social groups of children with special needs who are not only different but also lacking in certain aspects. This is also the case in Solo. This research doesn't just show the causes of marginalization, but also analyze it using the perspective of Rawlsian theory of justice and symbolic violence of Pierre Bourdieu. The method used is qualitative participation action research and collecting secondary data. The results showed that marginalization of children with special needs still occurs in educational environments, community environments, especially neighborhoods, even though there have been efforts to overcome it slowly. Substantial injustice mainly occurs in the provision of public facilities for children with special needs for inclusive education and environment. In addition, there are still found symbolic violence especially in families that is rarely realized and difficult to detect in the problem of marginalization of children with special needs.